Highly Specific and Effective Targeting of EGFRvIII-Positive Tumors with TandAb Antibodies - Ellwanger, Kristina; Reusch, Uwe; Fucek, Ivica; Knackmuss, Stefan; Weichel, Michael; Gantke, Thorsten; Molkenthin, Vera; Zhukovsky, Eugene A.; Tesar, Michael; Treder, Martin (Frontiers in Oncology, 2017)
To harness the cytotoxic capacity of immune cells for the treatment of solid tumors, we developed tetravalent, bispecific TandAb antibodies that recognize EGFRvIII, the deletion variant III of the epidermal growth factor receptor (EGFR), and CD3 on T-cells, thereby directing immune cells to eliminate EGFRvIII-positive tumor cells. Using phage display, we identified scFv antibodies selectively binding to EGFRvIII. These highly EGFRvIII-specific, fully human scFv were substantially improved by affinity maturation, achieving KDs in the picomolar range, and were used to construct a set of bispecific EGFRvIII-targeting TandAbs with a broad range of binding and cytotoxic properties. These antibodies exhibited an exquisite specificity for a distinguished epitope in the N-terminal portion of EGFRvIII, as shown on recombinant antigen in Western Blot, SPR, and ELISA, as well as on antigen-expressing cells in FACS assays, and did not bind to the wildtype EGFR. High affinity EGFRvIII/CD3 TandAbs were most potent in killing assays, displaying cytotoxicity towards EGFRvIII-expressing CHO, F98 glioma, or human DK-MG cells with EC50 values in the range of 1 pM – 10 pM in vitro. They also demonstrated dose-dependent growth control in vivo in an EGFRvIII-positive subcutaneous xenograft tumor model. Together with the tumor-exclusive expression of EGFRvIII, the EGFRvIII/CD3 TandAbs’ high specificity and strictly target-dependent activation with no off-target activity provide an opportunity to target tumor cells and spare normal tissues, thereby reducing the side effects associated with other anti-EGFR therapies. In summary, EGFRvIII/CD3 TandAbs are highly attractive therapeutic antibody candidates for selective immunotherapy of EGFRvIII-positive tumors.